2017
DOI: 10.22581/muet1982.1704.27
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Homemade Liquor “Tharra” Quality by GC-FID and its Potential Impacts on Human Health

Abstract: The unsafe use of alcohol causes many diseases that lead to social and economic burden in societies. In Pakistan due to limited access, inflated prices of standard alcohol and ban on use of alcoholic products for Muslims, the illegal Liquors "Tharra" production at domestic level is on the rise. The liquor (Tharra) contain many impurities and is often injurious to health. This study examines the impact of consumption of unsafe liquor on socioeconomic and health context in Pakistan by using primary data obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Further, an intensive hand hygiene campaign contributed to a significant reduction in influenza-related absence by 40% and diarrhea-related absence by 30%. Almost similar trial based study in Cairo, Egypt showed that the point-of-use water treatment and handwashing promotion intervention could reduce school absenteeism up to 35% and 26% respectively [21,22]. Therefore, taking our study as a baseline, further research may be initiated, and interventions should be made to avoid any health and education related emergency at HEIs.…”
Section: Students' Satisfaction Appraisalmentioning
confidence: 88%
“…Further, an intensive hand hygiene campaign contributed to a significant reduction in influenza-related absence by 40% and diarrhea-related absence by 30%. Almost similar trial based study in Cairo, Egypt showed that the point-of-use water treatment and handwashing promotion intervention could reduce school absenteeism up to 35% and 26% respectively [21,22]. Therefore, taking our study as a baseline, further research may be initiated, and interventions should be made to avoid any health and education related emergency at HEIs.…”
Section: Students' Satisfaction Appraisalmentioning
confidence: 88%